Metabolic and functional characterisation of adult skeletal muscle in down syndrome mouse model (Ts1CJe) for insights into hypotonia in human condition - Lim, Chai Ling (2017)
Down syndrome (DS) is a genetic condition resulting from a partial or full triplication of human chromosome 21. In addition to intellectual disability, DS is frequently associated with hypotonia. However, little is known about its underlying mechanism. In this study, the trisomic Ts1Cje mouse, a DS murine model, was employed to explore the possible mechanisms of DS-associated hypotonia. The hypotheses of this study are the over dosage of trisomic genes disrupts the population size and the cellular functionality of trisomic Ts1Cje satellite cells, as well as, the metabolic pathways in trisomic Ts1Cje skeletal muscle. Eventually, they lead to hypotonia seen in DS. In order to determine the satellite cell population in trisomic Ts1Cje skeletal muscle, myofibres derived from the EDL of the adult trisomic Ts1Cje mice and its age-matched disomic wild-type control littermates were isolated. The associated satellite cells were then quantified by using immunostaining for Pax7 (a marker for quiescent satellite cells). The results showed no significant variation in terms of the satellite cell populations between the two genotypes, indicating that the depletion of satellite cell populations may not a primary cause of DS-associated hypotonia. Additionally, the average number of myonuclei present in each EDL myofibre of the trisomic Ts1Cje mice was also investigated. The data obtained suggest that there was no significant difference in the average number of myonuclei per myofibre genotypes between the two genotypes. This finding suggested the trisomic Ts1Cje myofibres are normal in size. Meanwhile, the intrinsic cellular functionality of satellite cells between the two genotypes was also determined. Satellite cells derived from the EDL of the two genotypes were isolated and cultured in high-serum containing conditioned medium. Subsequently, the in vitro self-renewal, proliferative and differentiation activity of these myogenic precursor cells were assessed at 24, 48 and 72 h after cell seeding. These progenies were distinguished on the basis of Pax7 and MyoD (a marker for activating satellite cells) expression patterns. Furthermore, the results (proliferation and differentiation potential) obtained were later validated using Ki67 (a marker for proliferating cells) and MyoD expression patterns. These findings demonstrated that there was no difference between the satellite cells of the two genotypes in their ability to self-renew, proliferate and differentiate, indicating that alteration of the cellular function of satellite cells is not a primary cause of DS-associated hypotonia. Additionally, the metabolic profiles of trisomic Ts1Cje skeletal muscle were also evaluated using a non targeted metabolomics strategy. The hydrophilic and hydrophobic metabolites present in gastrocnemius (GA) samples of the two genotypes were extracted using methanol/chloroform/water partitioning-based protocol and subsequently were characterised by using 1H NMR spectroscopy combined with multivariate data analysis. The findings revealed that guanidinoacetate, histidine, adenosine monophosphate and glutamine were found to be at lower levels in the trisomic Ts1Cje skeletal muscle, indicating that alteration of energy, glutamate and histidine pathway metabolism in trisomic Ts1Cje skeletal muscle may underlie the hypotonia seen in DS. In conclusion, the perturbation of metabolic profile resulted from the over dosage of trisomic genes is the primary cause of DS-associated hypotonia.